Somali Refugee Students In Canadian Schools: Postmigration Experiences - Ayoub, Mohamad; Zhou, George (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2021)
This paper reports on the postmigration experiences of a group of Somali refugee students attending public schools in a southwestern city in Ontario, Canada. The findings were drawn from a qualitative study conducted to investigate the participants’ postmigration experiences. Data were collected through semi-structured, one-on-one interviews with six participants. Study participants faced many postmigration learning difficulties and socio-cultural challenges. The findings show the strengths of the participants related to resiliency and perseverance. Educators, administrators, peer students, and members of the school community could play a central role in supporting Somali refugee students after resettlement. This paper proposes strategies and approaches to support educators and the school community in their work with refugee students of Somali background and other cultural backgrounds.